The Relationship Between the Availability of Sports Facilities in the Village with Community Participation in Sports in Kali Berau Village, Bayung Lencir District - Saputra, Dodi Hendra; Wardiah, Dessy; Junaidi, Ilham Arvan (Yayasan Sembilan Pemuda Indonesia, 2023)
There is a problem in the village at this time, namely the lack of community participation in sports. The problem is not yet clearly known or may be caused by the lack of maximum availability of sports facilities in Kali Berau Village, Bayung Lencir District. So this study is focused and aims to determine the relationship between the availability of sports facilities in the village with community participation in sports. The independent variable in this study is Sports Facilities (X) while the dependent variable is Community Participation in Sports (Y). The results showed that there was a partial relationship between each independent variable and the dependent variable. Stimuli, there is a relationship between the availability of sports facilities and the number of community participation in sports, all of which can be seen from the enthusiasm of many residents who exercise after the existing sports facilities are repaired and updated. Various factors must be considered, developed and optimized to increase community participation in sports because the community is very enthusiastic in sports when sports facilities in the village are well available and with support from the village government so that this research is expected to be used as a reference for policy makers in planning development and designing sports policies, especially in increasing community participation rates in exercising in the village.